2006
DOI: 10.1007/s00168-006-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Job search success and employability in local labor markets

Abstract: This paper considers the relationship between an unemployed person's employability and job search success. Using a broad employability framework (covering individual, personal and external demand, and other factors) the paper considers a range of demand and supply factors, that were generally identified in applied and theoretical literature, that influence success in getting employment. The model is then used to consider the competing efficient metropolitan labor market and the local labor demand hypotheses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 26 publications
0
45
0
9
Order By: Relevance
“…Moreover, as the standard SMH focuses exclusively on the way that low-skilled minority workers residing in inner cities are affected by distant job locations, more and more authors prefer the expression spatial/skill mismatch to depict the spatial disconnection between the residential locations of inner-city minorities and the locations of the low-skilled service sector and manufacturing jobs in the suburb (Gobillon et al, 2007). Empirical studies on SMH by Bauder and Perle (1999), Immwegluck (1998), McQuaid (2006, Ong and Blumenberg (1998) all confirm that a disadvantage for blacks exists as a combination of spatial and skill mismatches.…”
Section: Spatial Mismatch Hypothesismentioning
confidence: 98%
“…Moreover, as the standard SMH focuses exclusively on the way that low-skilled minority workers residing in inner cities are affected by distant job locations, more and more authors prefer the expression spatial/skill mismatch to depict the spatial disconnection between the residential locations of inner-city minorities and the locations of the low-skilled service sector and manufacturing jobs in the suburb (Gobillon et al, 2007). Empirical studies on SMH by Bauder and Perle (1999), Immwegluck (1998), McQuaid (2006, Ong and Blumenberg (1998) all confirm that a disadvantage for blacks exists as a combination of spatial and skill mismatches.…”
Section: Spatial Mismatch Hypothesismentioning
confidence: 98%
“…The importance of labour demand and urban form are widely recognised as influencing commuting directly (Manaugh et al, 2010;McQuaid et al, 2001;McQuaid 2006) and may also indirectly influence commuting, for instance through wages. In Switzerland Kriesi et al (2010) found that job opportunities were strongly dependent on occupational credentials whereas educational attainment played a minor part.…”
Section: Introductionmentioning
confidence: 99%
“…In the workplace, a study by Purcell and colleagues (2002) [19] highlighted the particular importance some employers place on generic skills (such as communication skills and team-working). The findings of McQuaid, (2006 ) [15] suggest that professional qualifications, -soft‖ verbal skills and using speculative applications to employers were significantly related to job search success. Gracia, L. (2009) [8], has recognized, sandwich participation and employer's involvement in course design and delivery are positively associated with an occupation-based measure of the quality of initial employment found by graduates.…”
Section: Importance Of Communication and Behavioral Skills In Employamentioning
confidence: 98%